Biotechnological aspects of cytoskeletal regulation in plants - Komis, George; Luptovciak, Ivan; Doskocilova, Anna; Samaj, Jozef (Biotechnology advances, 2015)
The cytoskeleton is a protein-based intracellular superstructure that evolved early after the appearance of bacterial prokaryotes. Eventually cytoskeletal proteins and their macromolecular assemblies were established in eukaryotes and assumed critical roles in cell movements, intracellular organization, cell division and cell differentiation. In biomedicine the small-molecules targeting cytoskeletal elements are in the frontline of anticancer research with plant-derived cytoskeletal drugs such as Vinca alkaloids and toxoids, being routinely used in the clinical practice. Moreover, plants are also major material, food and energy resources for human activities ranging from agriculture, textile industry, carpentry, energy production and new material development to name some few. Most of these inheritable traits are associated with cell wall synthesis and chemical modification during primary and secondary plant growth and inevitably are associated with the dynamics, organization and interactions of the plant cytoskeleton. Taking into account the vast intracellular spread of microtubules and actin microfilaments the cytoskeleton collectively assumed central roles in plant growth and development, in determining the physical stance of plants against the forces of nature and becoming a battleground between pathogenic invaders and the defense mechanisms of plant cells. This review aims to address the role of the plant cytoskeleton in manageable features of plants including cellulose biosynthesis with implications in wood and fiber properties, in biofuel production and the contribution of plant cytoskeletal elements in plant defense responses against pathogens or detrimental environmental conditions. Ultimately the present work surveys the potential of cytoskeletal proteins as platforms of plant genetic engineering, nominating certain cytoskeletal proteins as vectors of favorable traits in crops and other economically important plants.
Keywords: interakce hostitele a patogenu; rostliny; Cytoskeleton; Plants; biotechnologie; Host-Pathogen Interactions; buněčná membrána; Biotechnology; buněčná stěna; Cell Wall; cytoskelet; Cell Membrane